2020
DOI: 10.1021/acs.energyfuels.0c02636
|View full text |Cite
|
Sign up to set email alerts
|

Pore-Throat Size Distribution and Classification of the Paleogene Tight Sandstone in Lishui Sag, East China Sea Shelf Basin, China

Abstract: The characteristics of tight sandstone reservoirs are closely influenced by the complex pore structure and the widths of pore-throat size distributions (P-TSDs). Because of the limitations of various techniques, it is difficult to characterize the morphology and size distribution jointly of the pore-throat structure. In this study, thin section, scanning electron microscopy, X-ray fluorescence diffraction, high-pressure mercury injection, and constant speed mercury injection were combined to analyze the pore t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The difference in dissolution in the study area depends on the intrusion of corrosive fluid and the changes in the opening and closing of the diagenetic system and is related to whether the acid-bearing body of organic matter can enter the reservoir smoothly [45]. The dissolution of the Pinghu Formation reservoirs is related to the Huagang Movement and the Longjing Movement [46]. Under the action of the Huagang Movement, when the oil and gas began to charge into the reservoir in the early stage, the organic acid fluid began to enter the reservoir.…”
Section: Accumulation Analysis Of Tight Sandstone Oil and Gasmentioning
confidence: 99%
“…The difference in dissolution in the study area depends on the intrusion of corrosive fluid and the changes in the opening and closing of the diagenetic system and is related to whether the acid-bearing body of organic matter can enter the reservoir smoothly [45]. The dissolution of the Pinghu Formation reservoirs is related to the Huagang Movement and the Longjing Movement [46]. Under the action of the Huagang Movement, when the oil and gas began to charge into the reservoir in the early stage, the organic acid fluid began to enter the reservoir.…”
Section: Accumulation Analysis Of Tight Sandstone Oil and Gasmentioning
confidence: 99%
“…Sr begins to precipitate at this time, and the Sr/Ba ratio in sediments will increase significantly. Therefore, it is feasible to judge the salinity of the sedimentary environment by the Sr/Ba ratio [20,[49][50][51]. It is generally considered that the Sr/Ba ratio of marine sediments is higher than that of continental sediments.…”
Section: Sr/bamentioning
confidence: 99%
“…Current research mainly concentrates on the Fuzhou Sag in the southern part of the ECS Shelf Basin, while the study of Mesozoic sedimentation in the Qiantang Sag, located in the centralsouthern part of the ECS Shelf Basin, is relatively scarce due to the extensive development of 'red beds'. As a significant component of the ECS Shelf Basin, the Qiantang Sag retains substantial Mesozoic sedimentary strata [6,[34][35][36][37], potentially rich in geological records related to plate subduction. This makes the study of its provenance and sedimentary evolution of great significance for a deeper understanding of the subduction history of the West Pacific margin and the development of the basin.…”
Section: Introductionmentioning
confidence: 99%
“…Gao Dezhang et al, based on the 1:200,000 gravity and magnetic results of the Qiantang area in the East China Sea, used techniques such as wavelet multi-scale decomposition and full magnetic latitude tilt angle polar conversion to determine the presence of Mesozoic strata in the Qiantang Sag area, and speculated the possible existence of Paleozoic strata [34]. Zhao Lei and Xia Qingqing, through their study of seismic profile stratigraphic frameworks, believe that the Qiantang Sag is a structural unit with Mesozoic-Cenozoic sedimentary infill, where the Cenozoic sedimentation is thin and of relatively small scale, and it has a distinct double fault structure [35,36]. Jiang Yiming et al, in their research on the edge structure of the Xihu Sag, found that the sedimentary strata of the Qiantang Sag can be traced in the seismic profile to the Pinghu Main Fault of the Xihu Sag, but due to limitations in seismic data quality, the contact relationship is difficult to confirm [37].…”
Section: Introductionmentioning
confidence: 99%